Risk of dementia and mild cognitive impairment in older people with subjective memory complaints: meta‐analysis. (13th September 2014) - Mitchell, A. J.; Beaumont, H.; Ferguson, D.; Yadegarfar, M.; Stubbs, B.
<x xml:space="preserve">Abstract</x> Objective To investigate whether people with subjective memory complaints (SMC) but no objective deficits are at increased risk of developing mild cognitive impairment (MCI) and dementia. Method Major electronic databases were searched till 03/2014, and a meta‐analysis was conducted using inception cohort studies. Results Across 28 studies, there were 29 723 unique individuals (14 714 with SMC and 15 009 without SMC) (mean 71.6 years) followed on average for 4.8 years through to dementia. The annual conversion rate (ACR) of SMC to dementia was 2.33% (95% CI = 1.93%–2.78%) a relative risk (RR) of 2.07 (95% CI = 1.76–2.44) compared with those without SMC (n = 15 009). From 11 studies the ACR of developing MCI was 6.67% (95% CI = 4.70–8.95%). In long‐term studies over 4 years, 14.1% (9.67–19.1%) of people with SMC developed dementia and 26.6% (95% CI = 5.3–39.7) went on to develop MCI. The ACR from SMC to dementia and MCI were comparable in community and non‐community settings. Conclusion Older people with SMC but no objective complaints are twice as likely to develop dementia as individuals without SMC. Approximately 2.3% and 6.6% of older people with SMC will progress to dementia and MCI per year.